Implementasi Manajemen Bandwidth pada Provider Internet dalam Peningkatan QoS - Hendra Gunawan (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Internet as the worldwide commercial data network and electronic commerce based is able to manage public data services, which includes intranet. There are some factors which make internet become important element in this communication era such as the increasing number of customers in the internet provider, speed of connection, traffic backbone. In addition, the finding of some new applications also has contribution to increase the important roles of internet itself. In facing competition, network operator dan Internet Service Provider (ISP) must provide good Quality of Service (QoS). Web based Bandwidth Management using Hierarchical Token Bucket (HTB) method could be the solution for the  achievement of expected QoS and in accordance with the needs of customers internet provider. Keywords : Bandwidth Management, QoS, HTB, Traffic Control.